2013
DOI: 10.1371/journal.pone.0074731
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium Mediated Transient Gene Silencing (AMTS) in Stevia rebaudiana: Insights into Steviol Glycoside Biosynthesis Pathway

Abstract: BackgroundSteviol glycoside biosynthesis pathway has emerged as bifurcation from ent-kaurenoic acid, substrate of methyl erythritol phosphate pathway that also leads to gibberellin biosynthesis. However, the genetic regulation of steviol glycoside biosynthesis has not been studied. So, in present study RNA interference (RNAi) based Agrobacterium mediated transient gene silencing (AMTS) approach was followed. SrKA13H and three SrUGTs (SrUGT85C2, SrUGT74G1 and SrUGT76G1) genes encoding ent-kaurenoic acid-13 hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…Plants exhibit phenotypic changes such as dwarfism and reduced internode length under reduced GA content (Thomas and Sun, ). It has been reported that transient knockdown of the SrUGT76G1 in Stevia led to an increase in GA levels so the overexpression of SrUGT76G1 may have an opposite effect (Guleria and Yadav, ). Hence, we monitored the growth and development of the transgenic Stevia plants.…”
Section: Resultsmentioning
confidence: 99%
“…Plants exhibit phenotypic changes such as dwarfism and reduced internode length under reduced GA content (Thomas and Sun, ). It has been reported that transient knockdown of the SrUGT76G1 in Stevia led to an increase in GA levels so the overexpression of SrUGT76G1 may have an opposite effect (Guleria and Yadav, ). Hence, we monitored the growth and development of the transgenic Stevia plants.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we characterize the function of these miRNAs. For this, we over-expressed miR319g and miRStv_11 in leaves of S. rebaudiana plant by syringe agroinfiltration method [5, 31] and the samples were collected after 2, 4, 6, 8 and 10 days post infiltration. Infiltration of over-expression construct corresponding to miRStv_11 was found to significantly up-regulate the expression of its target gene, KAH up to 8.16 fold than the control.…”
Section: Discussionmentioning
confidence: 99%
“…2) in determining SVgly total content (Kumar et al 2012;Guleria and Yadav 2013). UGT85C2, which catalyze the formation of steviol from kaurenoic acid and of steviolmonoside from steviol, might also be a rate limiting step for the SVgly biosynthesis route (Guleria and Yadav 2013;Mohamed et al 2011). On the other hand, the relative stability of the SVgly composition suggests that the UGTs are less regulated by the environment.…”
Section: Discussionmentioning
confidence: 99%